PERAN GURU DALAM PENANAMAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DI MTs PLUS NABAWI KEDUNGADEM BOJONEGORO - Ahsantudhonni; Ahmad Miftahul Ma’arif; Nursa Poppy Andriani (MIYAH : Jurnal Studi Islam, 2023)
Abstract: The role of teachers is very important in the learning process, not only general teachers, but religious teachers also have an equally important role in education, especially in instilling the values of Islamic Religious Education. This study aims to determine the role of teachers in instilling Islamic Religious Education values in MTs Plus Nabawi Kedungadem Bojonegoro and knowing the process of instilling Islamic Religious Education values in MTs Plus Nabawi Kedungadem Bojonegoro. This research uses a qualitative approach with a descriptive type of research. The results of the research on the role of teachers in instilling Islamic Religious Education values in MTs plus nabawi kedungadem bojonegoro include teachers as Guides, Motivators and Evaluators, therefore the role of teachers in instilling Islamic values is very important. The process of instilling Islamic Religious Education values is familiarizing students in dhuha prayers and congregational prayers, shaking hands every morning with teachers and getting used to polite language (fine Javanese) to anyone and anywhere, so that this habit is expected to be applied in the school environment and community environment. Keywords: The role of teachers, Instilling the values of Islamic Religious Education